Suffix –Ing in the Book of Romans The Holy Bible - Nugraheni, Maria Paskalia Putri; Bram, Barli (Language Circle: Journal of Language and Literature, 2023)
This article investigates the suffix –ing in The Book of Romans of The Holy Bible. This research belongs to a qualitative content with the use of descriptive design and distributional method to analyse gerunds, prepositions, and present participles as well as their functions as nouns, verbs, adverbs, and adjectives. The idea behind the distributional method is to identify morphemes through the distribution in various phrases or sentences. In this case, the data collected in this research was from The Holy Bible, specifically from The Book of Romans (Authorized King James Version) which contained 16 chapters. The Book of Romans consisted of various letters or epistles, written by the apostle Paul to the Christian church in Rome and aimed to give them direction, reassurance, and guidance. The results show that in a total of 115 words that the researchers found, 41 or 30% of them are gerunds functioning as nouns, 74 or 53% are present participles with 40 verbs, 3 adverbs, and 7 adjectives, as well as 24 or 17% prepositions.